Valores energéticos do gérmen integral de milho para aves de postura - De Lima, Michele Bernardino; Rabello, Carlos Bôa-Viagem; Da Silva, Edney Pereira [UNESP] (My University, 2016)
The aim of this study was to evaluate the effect of the substitution level of corn germ meal (CGM) on energy values obtained with Matterson's method and regression analysis. One hundred twenty laying hens from Embrapa 051 strain with 45 weeks of age, were used. The trial design was completely randomised, with five treatments and six replications of four birds. The treatments consisted of the reference feed (RF) and four other diets with dietary substitution levels of RF by CGM (10, 20, 30 and 40%). The method of total excreta collection was used. The variables analysed were: apparent metabolizable energy (AME), AME corrected for nitrogen balance (AMEn), time (T) and passage rate (PR) of the CGM. The relationship between the variables and levels of CGM was studied with regression analysis. The time and passage rate were linearly affected by the level of substitution of the CGM; with increases in the level of substitution. The values for AME and AMEn were reduced by 31.4% and 32.2% CGM respectively. The regression method provides better estimates for AME and AMEn of the CGM. In laying hens the CGM values for AME and AMEn were 5.161 and 5.066 kcal g-1, respectively.
Energy values of corn germ meal for laying hens
Keywords: Corn byproducts; Metabolizable energy; Passage rate